Toxicity and residual activity of insecticides against Palpita forficifera (Lepidoptera: Crambidae) - Tiago Scheunemann; Alexandra Peter Krüger; Aline Costa Padilha; Juliano Bastos Pazini; Dori Edson Nava; Daniel Bernardi (Ciência Rural)
ABSTRACT: Palpita forficifera Munroe is the main pest of olive orchards in Brazil. In the present study, we evaluated the toxicity of nine insecticides to 1st and 3st instar larvae and eggs of P. forficifera and the residual activity of insecticides when applied over olive trees for 3st instar larvae. In immersion bioassay, eggs immersed in insecticide solutions containing acetamiprid (Mospilan™ 200SP), chlorpyrifos (Pyrinex™ 480EC), and phosmet (Imidan™ 500WP) provided embryonic death of 100%. These insecticides, along chlorantraniliprole (Altacor™ 350WG), lufenuron (Match™ 50EC), novaluron (Rimon™ 100EC), spinetoram (Delegate™ 250WG), and zeta-cypermethrin (Mustang™ 350EC) caused mortality above 90% on larvae of 1st and 3st instar. Bacillus thuringiensis (Dipel™ SC) based insecticide provided death rates above 90% of P. forficifera first instar larvae. However, for 3st instar larvae death rate was 77%. Regarding median lethal time values (LT50), chlorpyrifos, phosmet, spinetoram, and zeta-cypermethrin presented higher toxicity to 1st (LT50 ≈ 5 h) and 3st (LT50 ≈8 h) instar larvae. However, the insecticide chlorantraniliprole caused residual activity for up to 49 days after application. However, until 35 days, acetamiprid, spinetoram, and phosmet provided larval mortality above 80%. Acetamiprid, B. thuringiensis, chlorantraniliprole, chlorpyrifos, lufenuron, phosmet, spinosad, and zeta-cypermethrin are viable P. forficifera management options.